A STUDY ON PROBLEMS FACED BY INVESTORS TOWARDS POSTAL SCHEMES WITH REFERENCE TO THOOTHUKUDI CITY - C. Maheshwari; S. Vanitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Based on their own savings, the investors are making the investment. Before making any investments, the investors will carefully review. Any form of investment that is to be made involves challenges for the investor.The postal scheme is a secure way to save money that offers consistent returns.This study examined the problems faced by investors while investing in postal schemes in Thoothukudi city. Garrett’s Ranking Method has been used to analyse the problems faced by investors. Primary data were collected from 104 sample investors through Questionnaire.